The women’s quality of life after bariatric treatment of morbid obesity - Rakhimberdyevich, Orazov Mekan; Borisovich, Elagin Ilia; Saulovich , Harnas Sergey; Borisovna, Khamoshina Marina; Ravilevna, Toktar Lilia; Eugenevich, Orekhov Roman; Alexandrovich, Semenov Pavel (International Journal of Psychosocial Rehabilitation, 2020)
The prevalence of morbid obesity has been found to be higher in women than in men. The article focuses on the quality of life of women suffering from morbid obesity